2000
DOI: 10.1006/viro.2000.0324
|View full text |Cite
|
Sign up to set email alerts
|

The Coxsackie-Adenovirus Receptor (CAR) Is Used by Reference Strains and Clinical Isolates Representing All Six Serotypes of Coxsackievirus Group B and by Swine Vesicular Disease Virus

Abstract: Group B coxsackieviruses are etiologically linked to many human diseases, and cell surface receptors are postulated to play an important role in mediating their pathogenesis. The coxsackievirus adenovirus receptor (CAR) has been shown to function as a receptor for selected strains of coxsackievirus group B (CVB) serotypes 3, 4, and 5 and is postulated to serve as a receptor for all six serotypes. In this study, we demonstrate that CAR can serve as a receptor for laboratory reference strains and clinical isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 29 publications
(51 reference statements)
5
107
0
1
Order By: Relevance
“…Therefore, as proposed for other viruses, the binding of SVDV to cellular GAGs probably mediates an early step of the virus-cell interaction, facilitating the subsequent recognition of other receptors such as CAR (Martino et al, 2000). However, it cannot be ruled out that HS is being used as an alternative receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, as proposed for other viruses, the binding of SVDV to cellular GAGs probably mediates an early step of the virus-cell interaction, facilitating the subsequent recognition of other receptors such as CAR (Martino et al, 2000). However, it cannot be ruled out that HS is being used as an alternative receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that, as in the case of coxsackievirus B1-6, the coxsackievirusadenovirus receptor (CAR) is a functional receptor for SVDV (Martino et al, 2000). Also, the decay-accelerating factor (DAF), used as co-receptor for coxsackievirus A21, B1, B3, B5, echovirus 6, 7, 11, and enterovirus 70 appears to have a role in SVDV entry into cells (Martino et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that even in the presence of the antibody, other non-insulin-producing islet cells are infected with CBV-5 in a less cytolytic way. For coxsackie B viruses, two different receptors, HCAR and DAF, have been identified in established cell lines, and especially serotypes 1, 3, 5 are known to use either or both as receptors [24,25,27,52,65]. An important role of HCAR in the development of coxsackievirus diseases has been suggested in recent studies on clinical virus strains characterised after only one passage through primary green monkey kidney cells [27,65].…”
Section: Discussionmentioning
confidence: 99%
“…This disruption resulted in a decrease in the TER of the monolayers from 4,767 Ϯ 398 ⍀⅐cm 2 to 190 Ϯ 29 ⍀⅐cm 2 . EDTA was replaced with medium alone, medium containing 5 g of the hCAR extracellular domain produced as an Ig-Fc fusion protein (soluble CAR) (17), or medium containing 5 g of the avian sarcoma virus Cell Adhesion Assay. Cells were trypsinized into a single cell suspension at a concentration of 1 ϫ 10 6 cells per ml and mixed gently at room temperature for 5 h. The number of aggregated cells (Ͼ2 cells contacting each other) was determined by using a hemacytometer.…”
Section: Methodsmentioning
confidence: 99%